Pengembangan Bahan Ajar (LKPD) Berbasis Problem Solving pada Materi Usaha dan Energi - Fartina Fartina; Badrul Wajdi (Kappa Journal, 2020)
This study aims to develop problem-solving based teaching materials (LKPD) with to business and energy materials. This type of research is development research / research and development. The development model used in this research is the 4D model, namely define, design, develop, and disseminate. Testing of problem solving-based student worksheet development products with a scientific approach is carried out through validation from material experts, media experts, subject matter teachers, and student questionnaire responses. The data technique used non-test (questionnaire and expert validation sheet). The technique of analyzing data from the distribution of questionnaires was carried out by tabulating the data from each validator, calculating the average score, and comparing the total score with a scale of five. Based on the results of 3 material experts, it shows that the quality of the LKPD is in the feasible category with a percentage value of 80%. Meanwhile, the results of 3 media experts show that the quality of LKPD is in the decent category with the proportion of the value of 77.15%. And based on the results of 2 subject teachers, it shows that the quality of the LKPD is in the decent category with a proportion of 82.5%. Meanwhile, the cost of student responses is in the very good category with an actual score of 78.4. DOI: 10.29408/kpj.v4i2.2680